2008
DOI: 10.1093/jpepsy/jsn056
|View full text |Cite
|
Sign up to set email alerts
|

Parent Quality of Life in the Context of Pediatric Inflammatory Bowel Disease

Abstract: Although as a group parental QoL was high, when youth are experiencing disease exacerbations or impaired QoL, parents may benefit from assessment and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 24 publications
5
25
1
Order By: Relevance
“…In the current study, the inclusion of fathers provided the opportunity to compare mother-and father-reported individual and family HRQoL and to investigate whether biological and psychological factors independently and differentially impact maternal and paternal perceptions of parent and family HRQoL. Consistent with Greenley and Cunningham's [20] findings, as youth disease activity increases, both mothers and fathers report lower HRQoL, and fathers report lower family HRQoL. Interestingly, disease activity is associated with all paternal outcomes, but only one of two maternal outcomes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the current study, the inclusion of fathers provided the opportunity to compare mother-and father-reported individual and family HRQoL and to investigate whether biological and psychological factors independently and differentially impact maternal and paternal perceptions of parent and family HRQoL. Consistent with Greenley and Cunningham's [20] findings, as youth disease activity increases, both mothers and fathers report lower HRQoL, and fathers report lower family HRQoL. Interestingly, disease activity is associated with all paternal outcomes, but only one of two maternal outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…Higher disease activity was associated with poorer maternal HRQoL in studies of mothers of youth with chronic illnesses such as diabetes and asthma [18,19]. Similarly, there is evidence to support a link between higher youth disease activity and lower mother HRQoL in pediatric IBD [20]. Although no studies have directly examined the relationship between disease activity and maternal perceptions of family HRQoL among pediatric IBD populations, Wood and colleagues [21] found that higher disease activity was associated with poorer family functioning.…”
Section: Impact Of Youth Disease and Adjustment Factorsmentioning
confidence: 99%
“…Recently, Greenley and Cunningham 74 performed a cross-sectional study of 49 IBD youths aged 10 -18 years and measured parental QOL using the RAND 36 Health Survey 1.0. This was the first study known to compare the parental QOL to that of a normative population.…”
Section: Family/social Supportmentioning
confidence: 99%
“…Chronic diseases in children impact not only the patients themselves but also their families including parents and siblings [4][5][6]8,[16][17][18][19] . Despite the fact that both chronic disease in the child and impaired QoL and psychosocial status of parent influences QoL in the sibling negatively, this area is not studied as extensively in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of this deterioration is associated with many different sociocultural and economic factors as well as social support 3 . Many previous studies have assessed the influence of child's chronic disease on QoL and psychosocial well-being of parents and caregivers and demonstrated impairment in many aspects such as sleep, social functioning, daily activities, vitality, positive emotions, and depressive emotions [4][5][6][7][8] . Similar psychosocial outcomes have been observed in siblings of children with a chronic disease and they were reported to have higher anxiety and depression as well as lower cognitive development and peer activities 9 .…”
mentioning
confidence: 99%